Rabies virus in white-nosed coatis (Nasua narica) in Mexico: what do we know so far? - Puebla-Rodríguez, Paola; Almazán-Marín, Cenia; Garcés-Ayala, Fabiola; Rendón-Franco, Emilio; Chávez-López, Susana; Gómez-Sierra, Mauricio; Sandoval-Borja, Albert; Martínez-Solís, David; Escamilla-Ríos, Beatriz; Sauri-González, Isaías; Alonzo-Góngora, Adriana; López-Martínez, Irma; et al. (Frontiers in Veterinary Science, 2023)
Rabies is a neglected disease that affects all mammals. To determine the appropriate sanitary measures, the schedule of preventive medicine campaigns requires the proper identification of the variants of the virus circulating in the outbreaks, the species involved, and the interspecific and intraspecific virus movements. Urban rabies has been eradicated in developed countries and is being eradicated in some developing countries. In Europe and North America, oral vaccination programs for wildlife have been successful, whereas in Latin America, Asia, and Africa, rabies remains a public health problem due to the habitation of a wide variety of wild animal species that can act as rabies virus reservoirs in their environment. After obtaining recognition from the WHO/PAHO as the first country to eliminate human rabies transmitted by dogs, Mexico faces a new challenge: the control of rabies transmitted by wildlife to humans and domestic animals. In recent years, rabies outbreaks in the white-nosed coati (Nasua narica) have been detected, and it is suspected that the species plays a significant role in maintaining the wild cycle of rabies in the southeast of Mexico. In this study, we discussed cases of rabies in white-nosed coatis that were diagnosed at InDRE (in English: Institute of Epidemiological Diagnosis and Reference; in Spanish: Instituto de Diagnostico y Referencia Epidemiologicos) from 1993 to 2022. This study aimed to determine whether white-nosed coatis might be an emergent rabies reservoir in the country. A total of 13 samples were registered in the database from the Rabies laboratories of Estado de Mexico (n = 1), Jalisco (n = 1), Quintana Roo (n = 5), Sonora (n = 1), and Yucatan (n = 5). Samples from 1993 to 2002 from Estado de Mexico, Jalisco, and Sonora were not characterized because we no longer had any samples available. Nine samples were antigenically and genetically characterized. To date, coatis have not been considered important vectors of the rabies virus. The results from our research indicate that the surveillance of the rabies virus in coatis should be relevant to prevent human cases transmitted by this species.